PO 18213 - Evaluation of hallux valgus treatment through percutaneous: systematic review - de Schoucair Jambeiro, Jorge Eduardo; Tavares Cordeiro Neto, Antero; Delmonte Moreira, Fernando; de Oliveira, José Augusto; Miguelino Sousa, Clara Cristiane; Fernande Leão, Felipe (Scientific Journal of the Foot & Ankle, 2019)
Introduction: Hallux valgus (HV) is characterized by the lateral deviation of the first finger, associated with pain and medial exostosis of the first metatarsus. The cause is usually multifactorial. The treatment varies with the degree of deformity and can be conservative or surgical. Percutaneous techniques have gained interest, offering less surgical trauma, fewer complications and faster recovery. The present study aims to evaluate the results of the surgical treatment of hallux valgus through percutaneous surgery. Methods: A search was performed in PubMed / Medline and BVS, from 2013 to 2018, using as descriptors "hallux valgus" and "percutaneous surgery". Original articles in English, Portuguese and Spanish were included. We excluded systematic reviews, descriptions of surgical technique and publications older than 5 years. The quality of the methodology was evaluated with the help of the STROBE tool, with an emphasis on hallux valgus (HVA), intermetatarsal angle (IMA) and the AOFAS score. Results: We found 185 references. After applying the inclusion and exclusion criteria, and STROBE tool, 5 articles were eligible, comprising a total of 290 percutaneous procedures. The follow-up time ranged from 6 months to 10 years. We found a reduction of IMA between 3.9º and 9.5º and a reduction of HVA between 12.5º and 26.8º. The AOFAS score ranged from 85 to 97.1 points in the evaluated works. Discussion: In general, we found a good correction of HV deformity with improvement of HVA, IMA, DMAA and clinical improvement by the postoperative AOFAS score, with low complication rates. However, the heterogeneity of the studies, with variation of techniques and samples did not allow us to generalize the findings. Conclusion: It was possible to note that percutaneous surgery for HV treatment produces good outcomes with low complication rates, but few studies had a high level of evidence demonstrating the efficacy of these techniques, despite encouraging preliminary results.